Kebijakan Kepala Madrasah dalam Meningkatkan Kompetensi Profesional Guru di MI NW Lendang Ara - Abdul Hafiz Alfatoni; Hamzani Aulia Rahman (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
This research aims to find out how the head of MADRASAH MI NW Lendang Ara made a policy in improving the professional competence of teachers. Policy is the fundamental basis for carrying out something with a specific purpose. This study uses qualitative, namely research conducted descriptively and analyze fe-nomena, events, social activities, attitudes, beliefs and perspectives of each person or group, while the data collection in this study using observations and interviews. This research was conducted at MI NW Lendang Ara, Kec. Kopang Central Lombok. In improving the professional competence of teachers the head of madrasah MI NW Lendang ara makes policies to make teacher training such as holding seminars, supervision, multi-disciplinary training and giving awards for teachers who excel and give freedom to teachers in developing themselves to increase their potential.